Is the Legislator in the Constitutional Court? Examining the Tension Between Judiciary and Democracy in Indonesia - Muttaqin, Labib; Omara, Andy; Atmoredjo, Sudjito; Fikri AR, M (Journal of Indonesian Legal Studies, 2025)
In cases of judicial review, the extension of the Constitutional Court's authority from negative to positive legislators contests the potential conflicts with democratic institutions, particularly parliament and the government. This study aims to analyze four key aspects: the legitimacy of the Constitutional Court in making Positive Legislature decisions, the conflicts that emerge between democratic institutions and the Constitutional Court due to the issuance of positive legislature decisions, Constitutional Courts as positive legislators in a comparative study, and the efforts undertaken to resolve conflicts. The research utilized a doctrinal legal research method, relying on secondary data gathered across literature pieces and analyzed qualitatively. The findings reveal that the Constitutional Court's decision to take on a positive legislator role has sparked conflicts between the courts and democratic institutions in Indonesia. This conflict was exemplified when parliament and the government withstand Constitutional Court Decision No. 91/PPUU-XVIII/2020, which declared certain provisions of Law No. 11 of 2020 on Job Creation somehow conditionally unconstitutional. Viewed from a global perspective, the Constitutional Court's role as a positive legislator also challenges democracy issues in many countries. To mitigate such conflicts, it is crucial to establish a mutual understanding among the Constitutional Court, parliament, and the government regarding the guidelines that the Constitutional Court should follow while making positive legislature decisions and the implementation by parliament and the President.